MENGUKUR KEPUASAN PELAYANAN PUBLIK INSTITUSI PEMERINTAH: STUDI KASUS PADA BUMN PT. JAMSOSTEK (PERSERO) - Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
Improving the service quality is not an easy task, especially if several parties are involved in the service delivery. Health Service Assurance (JPK) Program represents a type of public service on health conducted by PT Jamsostek (Persero). The program engages three parties: PT Jamsostek (Persero) as the host agency, provider as the health service delivering agent, and users as the clients comprising of institutions and their employees. Each party has its own shortcomings. The interaction of the three parties would raise further problematic issues than influence the service quality. This research is conducted to measure customer’s satisfaction toward the health service delivery.